Development and evaluation of time-resolved rapid immunofluorescence test for detection of TSOL18 specific antibody in porcine cysticercosis infections - Dejia Zhang; Rui Duan; Jing Liu; Mengqi Wang; Yi Yang; Yongjun Zhao; Mingyuan Liu; Shumin Sun (BMC Veterinary Research, 2024)
Abstract Background Porcine cysticercosis, a serious zoonotic parasitic disease, is caused by the larvae of Taenia solium and has been acknowledged by the World Organization for Animal Health. The current detection methods of Cysticercus cellulosae cannot meet the needs of large-scale and rapid detection in the field. We hypothesized that the immunofluorescence chromatography test strip (ICS) for detecting Cysticercus cellulosae, according to optimization of a series of reaction systems was conducted, and sensitivity, specificity, and stability testing, and was finally compared with ELISA. This method utilizes Eu3+-labeled time-resolved fluorescent microspheres (TRFM) coupled with TSOL18 antigen to detect TSOL18 antibodies in infected pig sera. Results ICS and autopsy have highly consistent diagnostic results (n = 133), as determined by Cohen’s κ analysis (κ = 0.925). And the results showed that the proposed ICS are high sensitivity (0.9459) with specificity (0.9792). The ICS was unable to detect positive samples of other parasites. It can be stored for at least six months at 4℃. Conclusions In summary, we established a TRFM-ICS method with higher sensitivity and specificity than indirect ELISA. Results obtained from serum samples can be read within 10 min, indicating a rapid, user-friendly test suitable for large-scale field detection.